Doctor Who : borrowed time - Alderman, Naomi; Prentis, Nicola; Linley, Adam (London : Penguin books, 2019)
Andrew Brown works at a big international bank. He makes lots of money every day, but he never has enough time. Now, he might have found a way to borrow some. But, instead of making his life easier, more time might just give him more problems. Maybe the time-travelling Doctor can help!
ADU
Keywords: Aventuras; Ciencia ficción